2019
DOI: 10.1111/febs.15135
|View full text |Cite
|
Sign up to set email alerts
|

PLAG enhances macrophage mobility for efferocytosis of apoptotic neutrophils via membrane redistribution of P2Y2

Abstract: Neutrophil activity, including trapping of damage-associated molecular patterns by neutrophil extracellular traps (NETs), is an important response to microbial infection. Most activated neutrophils commit to apoptosis and are removed by activated macrophages in the process of efferocytosis. Improper clearance of apoptotic neutrophils often causes an unnecessary and exaggerated immune response and subsequent chronic inflammation. Effective macrophage mobility toward activated neutrophils, which is triggered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…For resolution of gouty inflammation, macrophages perform essential process called efferocytosis to eliminate dead neutrophils and aggregated NETs. We already verified that PLAG promotes macrophage efferocytosis by enhancing macrophage mobility via membrane redistribution of P2Y2 (67). From the results, we expect that PLAG can help resolving of acute gouty inflammation by promoting efferocytosis.…”
Section: Discussionsupporting
confidence: 61%
“…For resolution of gouty inflammation, macrophages perform essential process called efferocytosis to eliminate dead neutrophils and aggregated NETs. We already verified that PLAG promotes macrophage efferocytosis by enhancing macrophage mobility via membrane redistribution of P2Y2 (67). From the results, we expect that PLAG can help resolving of acute gouty inflammation by promoting efferocytosis.…”
Section: Discussionsupporting
confidence: 61%
“…PLAG therapy has been shown to mitigate the effects of various diseases. Recent reports have documented that PLAG controlled neutrophil recruitment by regulating the trafficking of Toll-like receptors and enhanced efferocytosis through membrane redistribution of G protein-coupled receptors (45,46). We believe that these published studies have shown the ability of PLAG to modulate the movement of receptors, thus we hypothesized that PLAG may also modulate the trafficking of receptor tyrosine kinases (RTKs).…”
Section: Discussionmentioning
confidence: 97%
“…Neutrophils can be inactivated via apoptosis, forming apoptotic cells that are removed by tissue-resident macrophages through an efferocytotic mechanism (Maimon et al, 2020;Sekheri et al, 2020). It was reported that culture of macrophages or monocytes with apoptotic neutrophils increased the levels of IL-10 and TGF-β (Kim et al, 2019), while their engulfment enhanced the release of specialized pro-resolving mediators, such as lipoxin B4 and resolvin 1/2, indicating the potential anti-inflammatory action of apoptotic neutrophils (Sun et al, 2015;Moges et al, 2018). Additionally, neutrophil efferocytosis guided by phagocytic signals was found to be regulated by urokinase receptorassociated procedures (Park et al, 2009).…”
Section: Efferocytosis and Neutrophilsmentioning
confidence: 99%